Testando a cointegraç\~ao entre os fundamentos e a taxa real de câmbio: Evidências para países selecionados - Priscila Fernandes Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This study aims to test the existence of cointegration between variables that are typically used to estimate the existence of exchange rate misalignment for a sample of developed and developing countries, many of whom are members of the G20. The methodology consists in cointegration analysis using the procedure of Chen and MacDonald (2010), without the need to estimate a structural model. Compare the results with the results presented in Marçal (2012).
Keywords: F31; C32; 330; exchange rates; exchange rate misalignment; G20